The unrestricted global efort to complete the COOL trial - Andrew, W. Kirkpatrick; Federico, Coccolini; Matti, Tolonen; Samuel, Minor; Fausto, Catena; Emanuel, Gois Jr.; Christopher, J. Doig; Michael, D. Hill; Luca, Ansaloni; Massimo, Chiarugi; Dario, Tartaglia; Orestis, loannidis; et al. (BioMed Central Ltd., 2023)
Severe complicated intra-abdominal sepsis (SCIAS) has an increasing incidence with mortality rates over 80% in some settings. Mortality typically results from disruption of the gastrointestinal tract, progressive and self-perpetuating bio-mediator generation, systemic inflammation, and multiple organ failure. A further therapeutic option may be open abdomen (OA) management with negative peritoneal pressure therapy (NPPT) to remove inflammatory ascites and attenuate the systemic damage from SCIAS, although there are definite risks of leaving the abdomen open whenever it might possibly be closed. This potential therapeutic paradigm is the rationale being assessed in the Closed Or Open after Laparotomy (COOL trial) (https://clinicaltrials.gov/ct2/show/NCT03163095). Initially, the COOL trial received Industry sponsorship; however, this funding mandated the use of a specific trademarked and expensive NPPT device in half of the patients allocated to the intervention (open) arm. In August 2022, the 3 M/Acelity Corporation without consultation but within the terms of the contract canceled the financial support of the trial. Although creating financial difficulty, there is now no restriction on specific NPPT devices and removing a cost-prohibitive intervention creates an opportunity to expand the COOL trial to a truly global basis. This document describes the evolution of the COOL trial, with a focus on future opportunities for global growth of the study.